The mindfulness aspects in the teaching of culinary art in vocational high school - Nur Faizal Adkha; Putu Sudira; Ranu Iskandar (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aims to describe the aspects of mindfulness in the teaching of culinary art in vocational high schools. The aspects of mindfulness in the field of teaching consist of novelty, variety, joyfulness, meaningfulness, and alertness in learning. The benefits of mindfulness are related to the competencies in creativity, communication, collaboration, and critical thinking. These competencies are often referred to as the